Circulating KL-6 levels in patients with drug induced pneumonitis. Issue 10 (26th September 2003) - Ohnishi, H; Yokoyama, A; Yasuhara, Y; Watanabe, A; Naka, T; Hamada, H; Abe, M; Nishimura, K; Higaki, J; Ikezoe, J; Kohno, N
Abstract : Background: The circulating level of KL-6/MUC1 is a sensitive marker for various interstitial lung diseases. Previous case reports have suggested that KL-6 may also be increased in some patients with drug induced pneumonitis. A study was undertaken to determine whether serum KL-6 could be a marker for particular types of drug induced pneumonitis. Methods: The findings of high resolution computed tomographic (HRCT) chest scans of 30 patients with drug induced pneumonitis were reviewed separately by two independent observers. The pneumonitis was classified into four predominant patterns: widespread bilateral consolidation (diffuse alveolar damage, DAD; n=7), fibrosis with or without consolidation (chronic interstitial pneumonia, CIP; n=11), consolidation without fibrosis (bronchiolitis obliterans organising pneumonia or eosinophilic pneumonia, BOOP/EP; n=8), and diffuse ground glass opacities without fibrosis (hypersensitivity pneumonitis, HP; n=4). Serum KL-6 levels were measured by a sandwich enzyme linked immunosorbent assay. Results: The overall sensitivity of serum KL-6 in detecting drug induced lung disease was 53.3%, which was lower than its sensitivity in detecting other interstitial lung diseases. However, the KL-6 level was increased in most patients with a DAD or CIP pattern (16/18; 88.9%) and was closely correlated with their clinical course. In contrast, serum KL-6 levels were within the normal range in all patients with a BOOP/EP or HP pattern. Conclusions: Particular patterns detected by HRCT scanning, such as DAD and CIP but not the BOOP/EP or HP patterns, are associated with increased circulating KL-6 levels in drug induced pneumonitis. Serum KL-6 levels may reflect the clinical activity of the particular disorders.